STUDENTS’ KNOWLEDGE WITH ANXIETY IN THESIS COMPILATION ON EIGHTH SEMESTER STUDENTS S1 NURSING STUDY PROGRAM (Study at STIKES Insan Cendekia Medika Jombang) - Anggun Ayu Palupi; Marxis Udaya; Inayatur Rosyidah (STIKES Insan Cendekia Medika Jombang, 2014)
The last semester students’ knowledge of thesis was the knowledge that can be reference in thesis compilation. Problem of thesis compilation could be a threat so it can make anxiety. From the preliminary study results on S1 Nursing students’ of STIKES ICME Jombang compiling thesis was obtained 11 students had good knowledge about thesis compilation, 6 enough and 3 less. And 16 students were anxious and 4 students were not anxious. From 16 anxious students experienced sleep disturbance, 10 students were headache, 13 experienced appetite disorders and 4 were irritability. The purpose of the study was to analyze students’ knowledge with anxiety in thesis compilation on eighth semester students S1 nursing study program at STIKES ICME Jombang. Analytical study method used cross sectional approach. Population was S1 eighth semester students of nursing compiling thesis at STIKES ICME Jombang as many as 110 students, while the sample was majority of student as many as 33 students with proportional random sampling technique and in doing on 23 June, 2014. Independent variable was students’ knowledge about thesis compilation and the dependent variable was students’ anxiety. The instruments used questionnaires. Data processing used editing, coding, scoring, and tabulating. Data analysis used Spearmean test of SPSS17 with error rate α=0,05. Based on the study result, Respondents had good knowledge as many as 10 (30.3%), 12 enough (36.4%) and 11 less (33.3%). And respondents had mild anxiety as many as 12 (36.4%) , 17 moderate (51.5%) and 4 heavy (12.1). Statistical test result of Spearmean was obtained ρ=0,017 if α=0,05, so ρ<α so H1 was accepted. It can be concluded that there was relationship between students’ knowledge with anxiety in thesis compilation on eighth semester students S1 nursing study program at STIKES ICME Jombang.Keywords : Knowledge, Anxiety, Thesis, Students